Mythopoetics of Piano Nocturnes by Olena Ilnytska - Yakymchuk, Olena (Universitas Negeri Semarang, 2025)
A myth is one of the forms of worldview, a system of thinking, and a methodological basis for the interpretation of cultural phenomena. The mythological component is one of the elements of modern music culture. The article focuses on Olena Ilnytska’s piano nocturnes in the context of mythopoetic comprehension of musical texts. The article aims to analyze the characteristic features of Ilnytska’s piano nocturnes and identify the specifics of mythopoetic thinking of the composer. Piano nocturnes by Ilnytska are resented for the first time in the contemporary musicological discourse. The interdisciplinary approach embracing music, semiotics, and linguistics is used in the process of the study to analyze musical pieces comprehensively. The analysis of the piano Nocturnes by Ilnytska’s shows that the Nocturnes contain mythological thinking through the correspondence between cultural and sonority concept of different epochs (romanticism – metamodern). Thus, myth-making occurs when operating the set of binary oppositions, widening the technical capacities of the grand piano. The technical formulas combine traditional and unconventional ways of sound production. This research shows that the mythopoetic conception has entered into the contemporary cultural paradigm.